2019
DOI: 10.15240/tul/001/2019-4-010
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing consumer behaviour of Generation Y on the Czech wine market

Abstract: Consumer behaviour of Generation Y on the wine market is currently a topical issue. Generation Y is considered to be the future loyal consumers of wine and is therefore the future of the wine market. Wine-growing has a long tradition in the Czech Republic and, in particular, Moravian wines reach world level, as evidenced by a number of different awards and successes at winemaking competitions. The main aim of this paper is to identify the factors that affect the consumers of Generation Y when buying wine in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…Most of the participants answered that it was more likely to purchase wine from a supermarket, in agreement with a previous study [60], because supermarkets are accessible, easy to find and give the possibility to combine food with wine. Previous studies reported that many people accompany wine with meat, fish or nuts, while none of them preferred to consume it plain [59].…”
Section: Discussionsupporting
confidence: 90%
“…Most of the participants answered that it was more likely to purchase wine from a supermarket, in agreement with a previous study [60], because supermarkets are accessible, easy to find and give the possibility to combine food with wine. Previous studies reported that many people accompany wine with meat, fish or nuts, while none of them preferred to consume it plain [59].…”
Section: Discussionsupporting
confidence: 90%
“…On the contrary, the shape of the bottle, the harvest period, the label design or the wine-growing area have the least influence. Similar results were achieved in a Czech consumer study focused on the young generation (Generation Y), where the least important factor in wine selection was the shape of the bottle, the color of the wine and advertising (Němcová-Stanková, 2019). An interesting finding is the fact that factors, such as the country of origin and the producer also do not belong to the first half of the factors with a significant impact.…”
Section: Consumer Behaviour When Buying Winesupporting
confidence: 80%
“…Similarly, young Moldova consumers buy wine most often in super markets, then the neighboring shops and specialized wine shops [63]. The most common places for wine purchase are wine shops and supermarkets for Check consumers too [64].…”
Section: Discussionmentioning
confidence: 99%